Impact of Brand and Testing Method on Coffee Taste Perception between Genders: A Comparative Study of Two Leading Coffee Brands in Taiwan - Yi-Lang Chen; Ya-Chien Chen (SAGE Open)
Coffee is one of the world’s most widely enjoyed beverages and is sold by numerous global coffee brands; however, few studies have investigated how brand information affects the perceived tastes of consumers. This study employed three testing methods and subjective scoring to evaluate perceived coffee tastes associated with two popular coffee brands in Taiwan. Thirty young men and thirty young women were asked to drink Starbucks and 7-Eleven Americanos and then report their perceived preference levels under three method-related conditions (i.e., blind test [BT], correct brand information [CI], and incorrect brand information [II]). The analysis of variance results revealed that all the main variables’ effects on taste scores were nonsignificant and that the gender and brand variables interactively and individually affected the scores with the employed method. The overall taste score of the men was significantly higher than that of the women under the BT condition. Under the CI condition, women had a significantly higher preference for Starbucks Americano than for 7-Eleven Americano; this result was reversed under the BT condition. These findings suggest that the perceived taste of the female participants was influenced by the assimilation effect of coffee brands; however, this phenomenon was not observed in the male participants. This outcome can be attributed to the more sensitive taste of women relative to men. These insights are valuable for understanding the behavior of coffee consumers and for crafting effective service strategies tailored to coffee brand operators.